INOVASI PEMBELAJARAN AGAMA DALAM ERA DISRUPSI - Oktavianus Jeffrey Budiarto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2022)
Advances in information and communication technology have brought the world of education into a new era. Every student, especially in urban areas, has a gadget. They can easily and quickly navigate the virtual world, access information, socialize or have recreation with online games. They are comfortable spending time there. The audio visual design is so very tempting and catches their attention. Teachers and books are slowly getting overlooked. They prefer to look down at the screen and dissolve in virtual reality. This is the phenomenon of disruption that is hitting our world of education. The relationship between teachers and students is disturbed by the existence of gadgets with all the sophistication it offers. The era of disruption is an era of desacralization. Schools and teachers are no longer primary sources of knowledge. Like the jargon of a cellphone advertisement, now the world is in everyone's hands. The role of the teacher becomes relative in the search for "truth". Because students have got what they want to know with just a few clicks. It's faster, tends to be certain and can be done whenever and wherever he likes. Meanwhile, the teachers still hold tightly to the concept of three education centers, namely family, school and community. In fact, most of the children are active in cyberspace. An inevitable dimension of life exists and is real but is often overlooked. Teachers may often find students busy "playing cellphones" in class, uploads on social media that are so massive about their feelings. Although not infrequently there is also a talent for photography, art and positive expression. However, many parties are concerned about this as a threat.In my opinion, humans must always be the subject in all situations and conditions. So, responding to the phenomenon of disruption, as an educator, you must remain in a position of empowerment instead of feeling or allowing yourself to be deceived by gadgets that have already become a trend in students' lifestyles. Especially for religious teachers, students should not be influenced by negative content that can plunge them into pornography, spread provocations and hate speech, cyber crimes, and so on.This disruption phenomenon actually opens an opportunity for further learning exploration and learningdeep. Some of the things I have done are to invite students to criticize things that attract public attention on the internet related to religious, political and celebrity issues, use gadgets to create works (photos, videos, narrations) and upload them on social media. Like the cry of Saint Ignatius who reminded people to always try to find God in everything, so as educators we must try to help students find God and are sent to be bearers of glad tidings in virtual reality.